"N-factor/Anergic Margin" or resistance/susceptibility to hanseniasis I. The foundations of the theory - Abrahão ROTBERG (Hansenologia Internationalis, 1977)
The foundations of the pathogenetical theory "N-factor/Anergic Margin" postulated in 1937 and completed in 1957 are given. Based on the observation of 2.160 persons who had been tested by the author with Mitsuda's and frequently with other allergens, it was hypothesized that all individuals are born Mitsuda-negative but gradually become Mitsuda-positive with age, after stimulation by Hansen's mycobacterium, Myco tuberculosis BCG or other unknown agents, if they are capable of reacting, depending on the presence of a constitutional "natural" factor of resistance ("N-factor"). If infection occurs, the "N-factor" bearers resist, but tuberculoid lesions may appear if "accessory factors" coadjuvate. The minority, lacking the "N-factor", remains Mitsuda-negative throughout life ("Anergic Margin") and, if infected, may progress to the Virchowian aspects after the same coadjuvation. An extensive range of intermediate reactivities should be placed between both extremes of maximal hyperergy and maximal energy. The erythematous and/or hypochromic macule would be the theoretical initial stage of the tuberculoid, Virchowian and intermediate lesions. The theory contradicted Mitsuda's hypothesis of "exhaustion" of the Mitsuda-positivity to explain the energy of "nodular" (Virchowian) patients. It gave support to a genetical basis for predisposition to hanseniasis and was pessimistic about the preventive possibilities of BCG. The general acceptance of the theory — under its original or modified terminology (v.g. "Potential immunity', "Defect of cell-mediated immunity", etc.), the pending questions, and the field it represents for future research will be the subjects of following articles of this series.